Advanced energy storage technologies for renewable power systems: a comprehensive review - Tole Sutikno; Ahmad Raditya Cahya Baswara; Watra Arsadiando; Hendril Satrian Purnama; Mohd Hatta Jopri (Bulletin of Electrical Engineering and Informatics, 2026)
The accelerating deployment of renewable energy, particularly solar and wind power, has intensified the need for advanced energy storage systems (ESS) to address intermittency and enhance grid reliability. However, existing reviews often provide fragmented technology comparisons without a unified techno-economic framework for systematic evaluation. This paper presents a comprehensive review of studies published between 2011 and 2025, examining electrochemical, mechanical, thermal, and hydrogen-based energy storage technologies using four standardized metrics: round-trip efficiency (RTE), levelized cost of storage (LCOS), cycle life, and technology readiness level (TRL). Lithium-ion batteries (LIBs) demonstrate the highest maturity and efficiency (RTE: 90–95% and LCOS: 120–200 USD/MWh), whereas sodium-ion batteries offer promising cost reductions of 30–40% through abundant materials and scalable manufacturing. Pumped hydro and compressed air energy storage (CAES) remain suitable for large-scale applications owing to their long service life and scalability, while thermal energy storage (TES) provides cost-effective long-duration storage for concentrated solar power (CSP). Hydrogen-based storage, despite lower RTE (25–45%), offers unique advantages for seasonal energy balancing. Unlike previous reviews, this study integrates techno-economic performance with technology maturity through a TRL-oriented comparative framework, enabling systematic technology assessment based on deployment readiness, economic viability, scalability, and application suitability, thereby supporting informed decision-making and future hybrid energy storage development.